[OP.5A.02] SHORT AND LONG-TERM EFFECTS OF ANTIHYPERTENSIVE TREATMENT ON HUMAN RETINAL ARTERIOLE REMODELING EVALUATED WITH ADAPTIVE OPTICS CAMERA. (September 2016) - Gallo, A.; Rosenbaum, D.; Mattina, A.; Koch, E.; Kachenoura, N.; Paques, M.; Girerd, X.
Abstract : Objective: To evaluate the effects of blood pressure (BP) drop on retinal arteriole remodeling in hypertensive patients in a short-term vs long-term follow-up. Design and method: 57 hypertensive subjects without diabetes were consecutively enrolled and evaluated at baseline, 6 weeks (short-term) and 40 weeks (long-term). Among them, 28 had stable BP and 29 had BP drop after prescription of antihypertensive therapy after baseline visit. Adaptive Optics Camera using RTX1® (ImagineEye, Orsay, France) was used to measure Wall Thickness (WT), Internal Diameter (ID), Wall Cross Sectional Area (WCSA) and Wall-to-Lumen Ratio (WLR). Results: In the group of patients with "BP drop" at baseline, mean SBP/DBP, WT, ID, WLR and WCSA were 157/86 mmHg, 24.7 ± 4.7 μm, 73.3 ± 8.8 μm, 0.342 ± 0.07 and 3352 ± 943 μm 2 respectively. At short and long-term follow up SBP decrease was – 13% and −21% and DBP −7% and −12%, respectively. In this group, while WCSA remained stable at 6 weeks a statistically significant reduction in WLR (−6%) was observed due to lumen dilatation (+2.4%) and wall thinning (−4%). After 40 weeks also, while WCSA still remained stable, a further WLR decrease was observed compared to baseline (−11%) also related to both further lumen dilatation (+5.6%) and arterial wall thickness decrease (−6.5%). No changes in BP or in retinal arteriole anatomical indices were observed in patients with a stable BP throughout. Conclusions: After antihypertensive treatment induced BP drop, the observed WLR decrease is due to lumen dilatation and wall thinning without any significant WCSA change. This suggests that this retinal arteriole reverse eutrophic remodeling depends on changes in BP and myogenic tone, wall components rearrangements more than on wall mass changes.